Toolkit for Population Health Initiatives Around the Globe Related to Collaborative Comprehensive Medication Management for Children and Youth - Richard H. Parrish; Johannes van den Anker (MDPI AG, 2019)
Almost 30 million babies worldwide are born prematurely or become ill annually and need specialized care to survive. Formalized collaborative practice agreements (CPA) between clinical pharmacists and physicians have been put forward as a means for improving the overall medicating experience in many patient populations, including children. This report briefly describes opportunities for collaboration using examples from countries on each continent where CPA is established in professional governance documents and standards. It also provides resources in the form of a toolkit for countries and pharmacist–physician collaborators to authorize and form CPAs to provide comprehensive medication management (CMM) for children and youth with special health care needs (CSHCN).